Pengaruh Kualitas Pelayanan dan Citra Perusahaan Terhadap Loyalitas Nasabah Bank Mandiri Cabang Arief Palembang - Muhammad Gilang Saputra; Hanifati Intan; Neneng Miskiyah (Politeknik Negeri Sriwijaya, 2021)
This research was conducted at Bank Mandiri Branch Arief Palembang to determine whether service quality and company image affect customer loyalty. This research method uses a descriptive method with a quantitative approach. In the data collection technique using random sampling and sampling using the slovin formula with a total of 100 respondents who are customers of Bank Mandiri Arief Palembang Branch. The analysis technique in this study was carried out by t-test and f-test and assisted with SPSS data calculator. The results of this study indicate that service quality partially affects customer loyalty, service quality partially affects customer loyalty. Service quality and corporate image simultaneously affect customer loyalty F-count value of 3018.689 > 3.09 f-Table, with a significance value of 0.000 <0.05